Development and Validation of the NAI (Narration–Animation–Interactivity) Framework for PowerPoint-Based Procedural Writing in Elementary Schools - Ina Maryana; Dian Indihadi (International Journal of Nusantara Islam, 2026)
This study aims to develop learning media based on the NAI (Narrative, Animation, Interactivity) framework, using Microsoft PowerPoint, that meet the criteria of validity, practicality, and effectiveness to improve the writing skills of third-grade elementary school students in procedural texts. The background of this study is the low achievement in students' writing skills, with 65% not meeting the Minimum Completion Criteria (KKM). The study used the ADDIE development model and was conducted at SDN I Cibanteng, Tasikmalaya, with 29 third-grade students as subjects. The developed media integrates audio narration for verbal explanation, animation to visualize procedural steps, and interactive features such as self-navigation and quizzes with automatic feedback. The validation results showed a very high level of feasibility, with assessments from material experts at 92.5% and media experts at 90.0%, both in the very feasible category. Practicality responses also showed positive results, with teacher assessments at 88.5% (very practical) and student assessments at 86.2% (very good). The effectiveness test showed a significant increase in the average score from pretest (M=32.5) to posttest (M=42.7), based on a paired t-test (t=12.34; p<0.001) and an N-Gain value of 0.66 (medium–high category). The learning completion percentage increased from 27.6% in the pretest to 86.2% in the posttest. These findings indicate that the NAI framework effectively bridges the gap in procedural writing learning through affordable, easy-to-implement technology, while enriching the application of multimedia theory in Indonesian elementary education.